The application of the Gable Computer Aided Design System to the production of architectural working drawings. - Cotera, Jorge ([Sheffield], 1981)
Tesis (master en artes)--University of Sheffield, 1981
Keywords: PROGRAMACION (COMPUTADORAS ELECTRONICAS); ARQUITECTURA -- PROCESAMIENTO DE DATOS; GRAFICOS POR COMPUTADORA; GABLE